2022
DOI: 10.1002/advs.202201541
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic Aminated Derivatives of [60]Fullerene as Potent Inhibitors of Tumor Growth and Metastasis

Abstract: Malignant proliferation and metastasis are the hallmarks of cancer cells. Aminated [70]fullerene exhibits notable antineoplastic effects, promoting it a candidate for multi‐targeted cancer drugs. It is an urgent need to reveal the structure–activity relationship for antineoplastic aminated fullerenes. Herein, three amphiphilic derivatives of [60]fullerene with clarified molecular structures are synthesized: TAPC‐4, TAPC‐3, and TCPC‐4. TAPC‐4 inhibits the proliferation of diverse tumor cells via G0/G1 cell cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…BALB/c mice were treated with Cy5-labeled Cur-F (Cur-F-Cy5) or Cy5-labeled F-Gly (F-Gly-Cy5) via tail intravenous injection, and their primary organs (heart, liver, spleen, lung, and kidneys) were harvested for imaging ex vivo at different time intervals. It was demonstrated that Cur-F-Cy5 and F-Gly-Cy5 were mainly distributed in liver and kidney tissues (Figure A,B), which is consistent with other fullerene-based materials. , And the distribution of Cur-F in the liver is significantly higher than that of F-Gly (Figure C), suggesting the liver-targeting effect of Cur-F. These most abundant Cur-F concentrations in the liver inspired the application of it on hepatic diseases.…”
Section: Results and Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…BALB/c mice were treated with Cy5-labeled Cur-F (Cur-F-Cy5) or Cy5-labeled F-Gly (F-Gly-Cy5) via tail intravenous injection, and their primary organs (heart, liver, spleen, lung, and kidneys) were harvested for imaging ex vivo at different time intervals. It was demonstrated that Cur-F-Cy5 and F-Gly-Cy5 were mainly distributed in liver and kidney tissues (Figure A,B), which is consistent with other fullerene-based materials. , And the distribution of Cur-F in the liver is significantly higher than that of F-Gly (Figure C), suggesting the liver-targeting effect of Cur-F. These most abundant Cur-F concentrations in the liver inspired the application of it on hepatic diseases.…”
Section: Results and Discussionsupporting
confidence: 78%
“…Furthermore, we investigated the intracellular antioxidative effects of Cur-F. First, the cytotoxicity of Cur-F was evaluated by coincubation with RAW 264.7 cells and L02 hepatocytes at different concentrations for 24 h. It was and F-Gly-Cy5 were mainly distributed in liver and kidney tissues (Figure 3A,B), which is consistent with other fullerenebased materials. 42,43 And the distribution of Cur-F in the liver is significantly higher than that of F-Gly (Figure 3C), suggesting the liver-targeting effect of Cur-F. These most abundant Cur-F concentrations in the liver inspired the application of it on hepatic diseases.…”
Section: Preparation and Characterization Of Cur-fmentioning
confidence: 97%
“…An assessment of their safety profile was carried out using cytotoxicity screening on normal fibroblasts (Wi-38), followed by a comparison of their anticancer potential with 5-fluorouracil (5-FU) against three selected cancer cell lines (Caco-2, MDA-MB 231 and HepG-2). Fullerene@CA nanocomposite fibers, loaded with fullerene concentrations (0.1, 0.3, and 0.5 mg.g −1 ), are initially used as prescription carriers for anticancer treatments because fullerene has anticancer properties—according to previous studies 50 52 . The effect of Fullerene@CA nanocomposite fiber as an anti-cancer material was revealed, and it began to be evaluated as a standalone drug for anti-tumor growth where Bacakova et.al.…”
Section: Resultsmentioning
confidence: 99%
“…Polymeric assemblies including spherical, star-like, or worm-like nanoparticles, vesicles, or other complex structures could perform numerous applications in drug carriers or nanoreactors because of their unique characteristics and stability in a water environment. The self-assembly of amphiphilic copolymers with both hydrophilic and hydrophobic building blocks have been studied extensively, and several ripe experiences have been summarized. However, besides amphiphilic copolymers, covalently linked organic–inorganic hybrid materials bearing organic polymer chains and inorganic units, such as carbon or metal nanoparticles, have attracted a lot of research interest. Among inorganic nanobuilding blocks, polymer chain-modified fullerene C 60 has been widely investigated. As one of the typical examples, a series of supramolecular nanoassemblies, including the core–shell structure, spherical nanoparticles (SNPs), and nanonetwork architectures could be constructed from isotactic (it-) and syndiotactic (st-) C 60 -end-capped poly­(methyl methacrylate)­s through adjusting the types of solvents and block ratios …”
Section: Introductionmentioning
confidence: 99%